Letramento digital em livros didáticos de Língua Portuguesa - Pires, Robson Miguel (2016)
This present study analyses whether the Portuguese textbooks contribute to students\' digital literacy. To accomplish this research, we have selected seven Portuguese books from the 6th grade (primary school, late years), approved by the Textbook Guide of the National Textbook Program (Portuguese for PNLD-2014). To analyse them, the background theoretical information is anchored in the field of digital literacy, supports discussion and in the study of discursive genders (digital). The methodology is qualitative with bibliographic and documentary bias. To apply it, we have built a table and a graph that rank the books with more digital terms. With these data, we have selected two books for analysis. Our results point out that they do contribute to the digital literacy of the students, with reading and writing activities focusing on the diversity of digital genera that circulates in the network society. However, this result is still little within the universe of the seven analysed books. If we extend this number for the 12 books that have been approved by the PNLD/2014, we observe that the result is even smaller. Therefore, Portuguese textbooks need to address more digital genera, because they do contribute to the digital literacy development of the students who live increasingly in a digital society.